A new chaos-based image encryption system - El Assad, Safwan; Farajallah, Mousa (Signal processing. Image communication, 2016)
During the last decade, a variety of chaos-based cryptosystems has been introduced to protect the content of the transmitted images. In this paper, we propose a new fast, simple, and robust chaos-based cryptosystem structure and we analyze its performances. The cryptosystem uses a diffusion layer followed by a bit-permutation layer, instead of byte-permutation, to shuffle the positions of the image pixels. Moreover, the permutation layer is achieved by a new proposed formulation of the 2D cat map that allows an efficient implementation, measured by the time complexity, in terms of arithmetic and logic operations, and also, in terms of clock cycles, of the key-dependent permutation process in comparison with the standard one. Hence, it provides a very fast diffusion process to spread the influence of a single bit over the others. The new cryptosystem includes a robust and uniform chaotic pseudo-random generator (a very simplified version of a generator published in our patent) to change the control parameters in each round of the encryption/decryption processes. The generator is highly nonlinear and produces robust sequences of discrete values having very long orbits. The proposed cryptosystem is defined on finite numbers, and its speed is faster than many chaos-based cryptosystems, while having a very high security level. The security analysis and the obtained simulation results show that the proposed cryptosystem is resistant to various types of attacks and it is efficient for hardware and software implementation. •The proposed chaos-based cryptosystem is a new and efficient structure•It is based on a binary diffusion layer, followed by a bit-permutation layer•The permutation is achieved by an efficient proposed formulation of the 2D cat map.•It has a shorter encryption, while having a very high level of security.•It is adequate for a software and hardware implementations (FPGA card or an ASIC